التطبيق العملي لنظرية امللكة اللغو ية فيتعلم اللغة العربية = The practical application of Malakah Theory in the learning of Arabic Language - Che Haron, Sueraya; Abdullah, Nurazzelena; Salim al Rawahi, Mohammed Mabrook; Mohammed Alobeidani, Mohammed Juma; Ahmat Syafri, Norazman (Department of Arabic Language Education, Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia., 2024)
Learning Arabic requires a practical approach and theory to ensure the desired results. This research explores the theory presented by Ibn Khaldun, "Linguistic faculty theory," which integrates the Arabic language into the learner's core until it becomes second nature. This paper used qualitative research methods to collect and analyze data by reviewing the literature on the subject, such as magazines, books, and others. The results revealed that the entire theory can be summarized into three main stages: input, storage, and output. The process begins with listening to Arabic, followed by memorization and practice. Ibn Khaldun based his theory on the belief that language serves the primary purpose of communication. By following the stages correctly, learners can ensure that the received language is as sound and pure as the language being expressed. The study calls for the widespread adoption of this theory across educational institutions through reforming curricula and teaching methodologies and enhancing extracurricular activities and educational facilities. The integration of a strong, pure, and solid Arabic language culture should also be considered when designing the Arabic language program, in addition to providing opportunities and an environment to practice it.